2000
DOI: 10.1097/00005392-200001000-00077
|View full text |Cite
|
Sign up to set email alerts
|

The Outcome of Stopping Prophylactic Antibiotics in Older Children With Vesicoureteral Reflux

Abstract: The majority of children did well following cessation of antibiotic prophylaxis despite persistent vesicoureteral reflux. Cessation of antibiotic prophylaxis is a reasonable option in a highly select patient population with reflux.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0
3

Year Published

2002
2002
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 23 publications
2
21
0
3
Order By: Relevance
“…According to these studies, discontinuation of CAP after being toilet-trained seems safe [3,[5][6][7][8]. Cooper et al [5] were the first to report the outcome regarding discontinuation of CAP for children with VUR. They observed 51 children with persistent VUR for an average of 3.7 years.…”
Section: Discussion/conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to these studies, discontinuation of CAP after being toilet-trained seems safe [3,[5][6][7][8]. Cooper et al [5] were the first to report the outcome regarding discontinuation of CAP for children with VUR. They observed 51 children with persistent VUR for an average of 3.7 years.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Discontinuation of CAP after being toilettrained is generally recommended [18] because several studies have reported good outcomes [3,[5][6][7][8]. However, other recommended timings for discontinuation of CAP is not well documented.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Die Annahme, dass mit zunehmendem Alter das Risiko neuer pyelonephritischer Narben abnimmt, hat zu der inzwischen vielerorts praktizierten Strategie geführt, nach länge-ren infektionsfreien Intervallen bei Mäd-chen die antibakterielle Prophylaxe auch bei persistierendem niedriggradigem VUR versuchsweise abzusetzen [9]. Nur wenige Studien existieren, die dieses Vorgehen rechtfertigen [1,5,14]. So konnte in einer retrospektiven Untersuchung von 196 Kindern mit bekanntem VUR gezeigt werden, dass es nach Absetzen der antibakteriellen Prophylaxe etwa genauso häufig zu Parenchymnarben kam wie zuvor unter Prophylaxe [14].…”
Section: Wie Lange Sollte Beim Vesikoureteralen Reflux Eine Antibakteunclassified
“…1 Primary vur occurs in 1-2% of the pediatric population and in 30-40% of children presenting with urinary tract infections (utis). [1][2][3][4][5] the association of vur, uti and renal parenchymal damage is well known. 6,7 renal parenchymal damage can be congenital or acquired.…”
Section: Introductionmentioning
confidence: 99%